Papel de fatores celulares indutores de resposta imune de padrão Th1 na produção e funções de anticorpos contra Neospora caninum - Silva, Mariana Ferreira (2017)
Neospora caninum is a protozoan, obligate intracellular parasite that belongs to the Apicomplexa phylum and causes neosporosis. This parasite has a significant relevance in veterinary medicine causing neuromuscular disease in dogs and repetitive abortions in cattle herds, contributing to affective and economic losses. Th1-based immune responses against N. caninum is one of the major responsible to control infection, inducing the release of effector molecules that limits parasite replication. In that context, this study aimed to define the role of key Th1-related molecules in the synthesis and functions of antibodies during exposure to N. caninum antigens. To evaluate the production and function of these antibodies, WT and genetically deficient mice for TLR2, MyD88, IFN-, IL-12, MHCII and iNOS were immunized with soluble antigens of N. caninum (NLA). Kinetics of serum samples during immunization were measured by indirect ELISA. Profile of antigen recognition were evaluated by immunoblotting and biological functions assays analyzed by complement-mediated lysis and opsonization. We observed that in the absence of crucial factors in induction of Th1 response (TLR2, IFN- e IL-12) specific production of IgM and IgG antibodies was not impaired. Mice MyD88-/-, MHCII-/- and iNOS-/- presented significant decrease in the levels of these antibodies and in antigenic recognition. That reduction in these groups directly reflected in compromised lysis and opsonization properties of the hyperimmune sera. So, we demonstrate that factors related to Th1 immune response as MyD88, MHCII and iNOS, are crucial to induce humoral immune responses against N. caninum.